Los archivos nacionales de la América hispana y su inmersión en Internet. Presencia, contenidos y disponibilidad informativa. - Amalia Más Bleda; Juan José Sánchez Baena; Celia Chaín Navarro (Nuevo mundo - Mundos Nuevos, 2007)
It is expected to know the real situation of the Hispano-American National Archives available in the Internet. The websites of these archival documentary institutions and their contents are evaluated and compared in detail according to a pre-established questionnaire composed of 11 sections and 95 items or elements. It is concluded that the majority (73.68%) is present in the Net, although there is little information provided by most of them. There is an urgent need to homogenize the presentation, the structuring and systematization of the offered funds.